Hearing on H.R. 3247, reauthorization of the Native American Program Act : hearing before the Subcommittee on Human Resources of the Committee on Education and Labor, House of Representatives, Ninety-ninth Congress, first session, on H.R. 3247, hearing held in Washington, DC, September 12, 1985. - United States. Congress. House. Committee on Education and Labor. Subcommittee on Human Resources. (Washington : U.S. G.P.O. : For sale by the Supt. of Docs., Congressional Sales Office, U.S. G.P.O., 1986)
"Serial no. 99-81." Mode of access: Internet.